Isotherm study of the biosorption of Cu (II) from aqueous solution by vigna subterranea (L.) verdc hull - Nharingo, Tichaona; Muzondo, Maria N.; Madungwe, Emaculate; Chigondo, Fidelis; Guyo, Upenyu; Nyamunda, Benias C. (International Journal of Scientific and Technology Research, 2016)
The removal of Cu(II) ions from aqueous solutions is critical to minimize its toxicity to both plants and animals. Vigna subterranea (l.) Verdc hull (VSVH) was investigated for its potential to remove Cu(II) ions from wastewaters. Batch equilibrium studies were carried out to optimize pH, contact time, and dosage at constant temperature (25 ± 1 oC) and agitation rate (180 rpm). The effect of initial Cu(II) ion concentration was investigated under optimized conditions (pH, 6; contact time of 60 minutes and dosage of 6 g/L) and the equilibrium data were analyzed using two parameter isotherms; Temkin, Langmuir and Freundlich models. The equilibrium data fitted the isotherms in the order; Langmuir > Freundlich > Temkin, all with R2 > 0.98. The biosorption of Cu(II) ions by VSVH was found to be favorable (0 < RL< 1 and 1/n < 1), endothermic, spontaneous (∆Go = -11.11 kJ/mol) and chemisorption in nature. Very high removal efficiency and maximum sorption capacity were realized indicating the viability of the removal of Cu(II) ions by the novel biosorbent. The use of VSVH for the removal of Cu(II) ions from wastewaters can be implemented as a standalone technology or coupled with the conventional methods in order to complement their wastewater cleaning potentials.